Penetapan Status Daerah Khusus Ibu Kota Negara dalam Mewujudkan Kesejahteraan Ummat - Rosidin, Utang (LP2M IAIN Palangka Raya, 2018)
This paper is aimed at investigating the status determination of State Capital City and its influence in establishing people welfare. The method used in this study is descriptive analysis method by explaining a whole general description and systematic phenomena occurred. Determination of territory becoming state capital city as a special territorial unit in accordance with Article 18B of the 1945 Constitution of the Republic of Indonesia is regulated by historical factor, regional needs factor, and regional atmosphere factor. Then, it is regulated through specific laws established by the government on the basis of philosophical, juridical, and sociological aspects. The regional government ofÂ capital city has an important role to achieve welfare, with various aspects of community life related to the aspects of justice, law enforcement, respect for human rights, acceleration of economic development, improvement and development for existed communities in the region, which is not only determined by the government, but also based on individual aspiration (citizens), especially the majority of Muslim communities, in order to realize the Indonesian nation in protecting the entire Indonesian nation, advancing general welfare, educating nation life, and involving in realizing people welfare.